Detection of canine visceral leishmaniasis by conjunctival swab PCR - Pereira, Vanessa Figueredo; Benassi, Julia Cristina; Starke-Buzetti, Wilma Aparecida [UNESP]; Silva, Diogo Tiago; Ferreira, Helena Lage; Keid, Lara Borges; Soares, Rodrigo Martins; Azevedo Ruiz, Vera Letticie de; Ferreira de Sousa Oliveira, Tricia Maria (Soc Brasileira Medicina Tropical, 2016)
Introduction: Conjunctival swab PCR was evaluated as a tool to diagnose visceral leishmaniasis in dogs. Methods: Conjunctival swab PCR was compared to indirect immunofluorescence antibody test and blood PCR. Results: Indirect immunofluorescence was significantly correlated with conjunctival swab PCR (p < 0.05), but not with blood PCR (p > 0.05). In addition, conjunctival swab PCR was significantly associated with presence of clinical symptoms (p < 0.05), whereas blood PCR was associated with absence of clinical symptoms (p < 0.05). Conclusions: Results indicate that conjunctival swab PCR is useful in epidemiological surveys of canine visceral leishmaniasis.
Keywords: Canine visceral leishmaniasis; Conjunctival swab; Epidemiological survey